Crimen en la colina : el primer caso de la familia Casadei - Flamigni, Carlo (Nuevos tiempos (Madrid, Spain), 2013)
Cousin Casadei, a writer of questionable past and his Chinese wife, Maria, move their family to Roman, a small town.They are hoping that the countryside weather would help Beatrice, one of their twin daughters recover from tuberculosis. But shortly after their arrival, the peaceful town is disturbed by several murders of children in the forest. The murders are so different from one another that Cousin decides to investigate on his own.